PENERAPAN MEDIA RODA PINTAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA SANGGAR BIMBINGAN SUNGAI MULIA MALAYSIA - Satria Pratama, Bagas; Kuswandi, Iwan; Armadi , Ali (Universitas Negeri Medan, 2024)
Abstract: This research was carried out at SBSM 5 Gombak Malaysia on 17-20 September 2024. The initial reading ability of grade 1 students at Sanggar Guidance Sungai Mulia (SBSM) Malaysia is low, so special attention is needed for teachers as educators to improve students' ability to read. The purpose of writing this article is to find out how the teaching and learning process at SBSM Malaysia is in learning Indonesian using the smart reading wheel learning media which is carried out using a qualitative approach with case study research and data sources using observation, interviews and documentation. The data collection process includes data reduction, data presentation, and drawing conclusions. The result of writing this article is that the smart reading wheel media is expected to make it easier for students to recognize letters and spell letters so that they can read word for word. Because of this, researchers are eager to conduct research and create media roda pintar to address the issue at hand through research with the title